ALMOST CONTRA G(b*g)* CONTINUOUS FUNCTION IN GRILL TOPOLOGICAL SPACES - Kanchana, M.; Kumaran, V. Senthil; Palaniappan, Y. (Journal of Advance Research in Mathematics and Statistics (ISSN 2208-2409), 2022)
The aim of the paper is to study a new class of almost contra continuous function called almost contra G(b*g)* continuous function. Its relation to other continuous functions are give.